Enhanced fatigue and durability of carbon black/natural rubber composites reinforced with graphene oxide and carbon nanotubes. (January 2020) - Guo, Hao; Jerrams, Stephen; Xu, Zongchao; Zhou, Yanfen; Jiang, Liang; Zhang, Liqun; Liu, Li; Wen, Shipeng
Highlights: Well-dispersed CNT-CB/NR and GO-CB/NR composites were prepared. Fibrous CNT and flaky GO effectively reduced the crack growth rate of CB/NR composites. GO-CB/NR composite showed long fatigue life under uniaxial and multi-axial cyclic loading. Abstract: Graphene oxide (GO) sheets and carbon nanotubes (CNTs) are of nanometer size and offer large shape factors which are beneficial in reducing crack propagation rates of composites when used in carbon black (CB) reinforced natural rubber (NR), thereby prolonging the service lives of rubber composites. In this research, CNT-CB/NR and GO-CB/NR composites were prepared by partially replacing CB with one-dimensional CNTs and two-dimensional flaky graphene oxide GO, respectively. The results showed that the complex filler dispersion in NR matrices was improved due to the isolation effect between the different fillers. The strain-induced crystallization (SIC) ability of CB/NR was effectively enhanced by the addition of both GO and CNT. The modulus at 100% strain and tear strength of the composites were also improved. More branching and deflections were observed at the crack tips of the composites and both effectively hindered crack propagation in the materials. Under uniaxial and multi-axial cyclic loading, the fatigue lives of CNT-CB/NR and GO-CB/NR composites greatly increased when compared with the fatigue lives of CB/NR composites. The GO-CB/NR composites exhibited evident advantages in respect of fatigue resistance and durability among the three composites.